Distinct NK cell function and gene expression in children with acute lymphoblastic leukemia in remission before and after acute exercise: an exploratory study - Plaza-Florido, Abel; Perlsteyn, Martin; Haddad, Fadia; Cooper, Dan M.; Bar-Yoseph, Ronen; Lucia, Alejandro; Radom-Aizik, Shlomit (Frontiers in Immunology, 2025)
BackgroundBrief bouts of exercise mobilize natural killer (NK) cells and influence their function and gene expression in adults. However, little is known about these effects in children with acute lymphoblastic leukemia (ALL) in remission. This study investigated the effect of acute exercise on NK gene expression and cytotoxic activity (NKCA) in children with ALL in remission.MethodsNine B-cell ALL children in remission and 9 age- and sex-matched healthy controls (14.8 ± 1 and 15 ± 1 y/o, respectively; 2 girls per group) performed an acute exercise session consisting of eight 2-min bouts of cycle ergometry at 60% of peak work rate (71 ± 2% of peak oxygen uptake) interspersed with 1-min rest intervals. Circulating NK-cell gene expression profile (RNA-seq) and NKCA (in vitro assay) were studied before and after the exercise session.ResultsAt baseline, 284 genes were differently expressed in children with ALL compared to controls, and 179 genes were differently altered by acute exercise in the ALL group (p<0.01). At baseline, nine gene pathways related to NK cell function were affected, while following exercise, 28 pathways associated with inflammatory response and cancer were impacted (FDR<0.05). NKCA following IL-2 stimulation was lower both at baseline (p<0.05) and after exercise (p=0.09) in ALL compared to controls. The impaired activity was partially mitigated following exercise but remained lower in ALL compared to controls.ConclusionsAcute exercise may improve NK cell function in ALL children in remission and has the potential to be used as adjunctive therapy in ALL. The differential gene expression response to exercise suggests that NK cells in ALL may adopt a different molecular strategy to fight infections or tumors.